(untitled) (Bangladesh Journal of Pharmacology, 2012)
This study was undertaken to validate the medicinal use of Chrozophora prostrata in constipation. The crude extract of C. prostrata produced laxative effect in mice at 100 and 300 mg/kg, similar to carbachol and castor oil. In spontaneously contracting rabbit jejunum tissues, C. prostrata (0.01-3 mg/mL) exhibited atropine-sensitive spasmogenic effect, which was reproducible in guinea-pig ileum. Interestingly, at high concentrations, C. prostrata showed concentration-dependent inhibitory effect on rabbit jejunum, suggesting the presence of accompanied spasmolytic activity. When tested on induced contractions, C. prostrata completely relaxed low K+-induced contraction, while partially inhibited high K+, similar to cromakalim. Tetraethylammonium pretreatment abolished the relaxant effect of C. prostrata on low K+-induced contractions while glibenclamide caused partial inhibition, suggesting the involvement of some non-specific and ATP-dependent K+ channels. These data show that C. prostrata possesses laxative effect at low doses mediated through cholinergic action followed by the spasmolytic activity at high doses mediated possibly through K+ channel activation.